First record of Sclerocactus papyracanthus (Cactaceae) in Mexico - Ortiz-Brunel, Juan Pablo; Delladdio, Aldo; Raya-Sánchez, Ricardo Daniel; Pérez-Badillo, Cristian; Zurita-Suárez, Iván; Flores, Joel (Instituto de Ecología, A.C., 2023)
Background and Aims: Sclerocactus (Cactaceae) is a genus that comprises 27 taxa mainly distributed in the southern United States of America and northern Mexico. Sclerocactus papyracanthus is a very distinctive species due to its flattened papyraceous central spines and its growth form, which is similar to that of some grasses. Its currently known distribution is in the states of Arizona, New Mexico, and Texas in the southern USA close to the border with Mexico. However, we detected an observation of a putative individual of this species in Chihuahua on the Naturalista platform. Therefore, we set out to find individuals of S. papyracanthus in Mexico, describe their morphology, its ecological preferences, and document their occurrence in this country with herbarium specimens, photographs, and illustrations.Methods: Using the location indicated in the Naturalista observation, we carried out two explorations in early 2023 to the state of Chihuahua in search of the species. A cactus population that resembled S. papyracanthus was found. We took photographs, measured and described the morphological characters of the found individuals, and prepared herbarium specimens. The obtained morphological and ecological data were compared with those reported in the scientific literature and with other available herbarium vouchers.Key results: The morphological comparisons corroborated that the Sclerocactus population found corresponded to S. papyracanthus and the presence of the species in Mexico was confirmed. A total of 38 plants of different sizes were found. Also, two young individuals flowering were documented. Conclusions: In Mexico, S. papyracanthus is now known from a single grassland locality in the municipality of Ascensión, Chihuahua. Further exploration and investigation are needed to understand its ecological preferences and its distribution in Mexico.